Profile and anticoagulation outcomes of patients on warfarin therapy in an urban hospital in Cape Town, South Africa - Sonuga, Babatunde O. (Afr J Prim Health Care Fam Med, 2016)
BACKGROUND: Warfarin is the most frequently used oral anticoagulant worldwide and it is the oral anticoagulant of choice in South Africa for reducing thrombosis-related morbidity and mortality. However, the safety and efficacy of warfarin therapy depends mainly on careful monitoring and maintenance of the international normalised ratio (INR) within an optimal therapeutic range. AIM: The aim of this study was to describe the profile and the anticoagulation outcomes of patients on warfarin therapy in a major warfarin clinic in the Western Cape Province of South Africa. SETTING: Victoria Hospital - a district hospital in Cape Town. METHODS: A cross sectional review of clinical records of patients on warfarin therapy who attended the INR clinic from 01 January 2014 to 30 June 2014 was done. Data analysis was done with STATA to generate appropriate descriptive data. RESULTS: Our study showed that atrial fibrillation (AF) was the commonest indication for warfarin use in this study and hypertension was the commonest comorbidity among these patients. Only 48.5% achieved target therapeutic range; 51.5% were out-of-range. There was a significant association between alcohol consumption and poor anticoagulation outcomes (p-value < 0.022). Anticoagulation outcomes were better among the older age groups, male patients and in those with AF. The prevalence of thrombotic events while on warfarin treatment was 2.2%, while prevalence of haemorrhagic events was 14%. Most of the patients with bleeding events were on concurrent use of warfarin and other medications with potential drug interactions. CONCLUSION: In our study, patients who achieved target therapeutic control were less than the acceptable 60%.